2018
DOI: 10.1002/ldr.2912
|View full text |Cite
|
Sign up to set email alerts
|

Early response ofQuercus roburseedlings to soil compaction following germination

Abstract: Logging operations using heavy machinery effect changes in soil characteristics due to compaction; such conditions can negatively influence seedling development. In stands managed on the basis of close‐to‐nature silviculture or continuous cover forestry, successful establishment of natural regeneration after logging is important to ensure the proper functioning of a forest ecosystem, to promote soil recovery, and to prevent and mitigate land degradation processes (such as soil erosion, mudflow, waterlogging, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 75 publications
(131 reference statements)
0
19
0
1
Order By: Relevance
“…Soil compaction caused by a forwarder may be more severe [20], which may lead to a slower early growth of seedlings [21]. Forest machines, and especially fully-loaded forwarders, cause unwanted soil disturbances [22], which is usually more intensive in older stands, where trees of bigger dimensions are extracted [23].…”
Section: Discussionmentioning
confidence: 99%
“…Soil compaction caused by a forwarder may be more severe [20], which may lead to a slower early growth of seedlings [21]. Forest machines, and especially fully-loaded forwarders, cause unwanted soil disturbances [22], which is usually more intensive in older stands, where trees of bigger dimensions are extracted [23].…”
Section: Discussionmentioning
confidence: 99%
“…The reduced development of root systems caused by soil compaction results in limited access to nutrients and water accompanied by lower photosynthetic rate [12]. A lower seedling establishment and survival and ultimately seedling growth and production was observed by Gebauer and Martinková [13], Naghdi et al [1], and Cambi et al [14] in compacted soils. However, the severity of these effects depends on soil type and tree species [15,16].…”
Section: Introductionmentioning
confidence: 93%
“…Gu et al (2019) reported that the volume density values should be taken as one of the indicators to assess the effect of vegetation restoration process on the physical properties of the soil. This is explained by the fact that even a slight increase in soil density has a significant negative effect on the growth and development of tree species, particularly oaks (Bejarano et al, 2010;Cambi et al, 2018;Kormanek et al, 2015).…”
Section: Effect Of Forest Plantations On Aggregate Size Distribution mentioning
confidence: 99%